Let's complete the process of solving the equation step by step.
Starting with the equation: \[ -2c + 16 = c + 1 \]
-
Add \(c\) to both sides (to get all terms involving c on one side): \[ -2c + c + 16 = 1 \] This simplifies to: \[ -1c + 16 = 1 \]
-
Subtract 16 from both sides (to isolate the term with c): \[ -1c + 16 - 16 = 1 - 16 \] This simplifies to: \[ -1c = -15 \]
-
Multiply both sides by -1 (to solve for c): \[ c = 15 \]
So the complete process of solving the equation is as follows:
Start with: \[ -2c + 16 = c + 1 \]
- Add \(c\) to both sides: \[ -2c + c + 16 = 1 \]
This results in: \[ -1c + 16 = 1 \]
-
Subtract 16 from both sides: \[ -1c = -15 \]
-
Multiply both sides by -1: \[ c = 15 \]
Therefore, the missing terms and descriptions can be filled in as such:
- 3c = \(-1c + 16 = 1\) (which should be adjusted to avoid confusion; the outcome is based on simplifying the previous steps)
- 15 = \(-15\) or directly \(= -15\) from isolating \(c\)
- Divide both sides by \(-1\).
Thus, the complete answer is: \[ c = 15 \]
It is also straightforward to note that:
- "Add c to both sides" → Step 1
- "Subtract 16 from both sides" → Step 2
- "Divide both sides by -1" → Final calculation to isolate \(c\).
Adjust or clarify if needed for planarity in description!